Effect Of 0.2% Chlorhexidine Gel in the Management of Postoperative Pain After Pre-Prosthetic Surgery: Pilot Study - Marcín-Montero, Claudina; Martínez-Aguilar, Víctor M.; Castillo-Bolio, Rubén; Mena-Porras, Esteban; Amaury Pozos-Guillén, Amaury; Larios-Cervantes, Alexis A.; Chavarría-Bolaños, Daniel (Odovtos - International Journal of Dental Sciences, 2025)
Pre-prosthetic surgical procedures such as clinical crown lengthening (CLS), can cause pain, discomfort, and postoperative inflammation; causing the need of the prescription of medications such as analgesic, anti-inflammatories and in certain cases systemic antibiotics. However, prolonged and indiscriminate use of these medications often leads to adverse effects on general health. Thus, the ideal to treat locally pain and inflammation, and to prevent local infection is promising. The objective of this preliminary study was to evaluate the controlled use of a local chlorhexidine gel (CHXg) immediately place after pre-prosthetic periodontal surgery to manage postoperative pain using a customized whitening trays. A randomized controlled double-blind parallel-group clinical pilot trial was conducted. A sample of 10 patients aged 18 to 60 years, requiring a crown lengthening procedure was selected. Two groups (Group A: 0.2% CHXg vs Group B: placebo gel). Pain scores were evaluated by using a visual analog scale (VAS), and side effects and poswas 3.32 for Group A and 4.85 for Group B (p=0.05), with results showing no statistically significant difference. Few studies have assessed the effect and influence of 0.2% CHX gel on postoperative pain control. Some reports suggest that intra-alveolar use of CHX gel is more effective than administering 10 mg of ketorolac alone. In this study, there were no statistically significant differences, indicating that the use of 0.2% CHX gel applied after pre-prosthetic surgery may not significantly reduce postoperative pain.